PEMANFAATAN SAMPAH PLASTIK MENJADI PRODUK BERNILAI JUAL DENGAN MODEL TRASHION - Siti Aisyah; Sura Menda Ginting; Eka Novita; Khairul Amri Rosa (DHARMA RAFLESIA, 2017)
Trashion is the activity of turning trash into fashion goods. The utilization of waste into valuable recycled products is an activity that should be done to save the environment andincome generating. This activity introduces how to process waste, designing, and makingproducts from plastics waste. This activity invites society to make use of waste, honingskills to design and sew and look at business opportunities from Trashion products.Keywords: Trashion, plastic waste, recycle, product design